THEMATIC PROGRESSION ANALYSIS IN BUSINESS COLUMN OF THE JAKARTA POST NEWSPAPER - Hiace Vega Fernando Siahaan (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
This study deals with thematic progression analysis in business column especially in a newspaper. The objectives of this study are to investigate the pattern of thematic progression in business column and to find out the most dominant used of thematic progression in business column in delivering the message. Thematic progression is used by the writer for linking the themes and rhemes in a clause in order to make the reader understand the message well. Theme is the point of departure for what the speaker is going to say. Meanwhile, rheme is the reminder of the message, the part in which the theme is misleading (Halliday, 1994: 37-38). This study was conducted by using descriptive qualitative study (Miles & Hubberman, 2014). The data of this study were taken from The Jakarta Post Newspaper especially the business column. Based on the analysis, it was found that the four types of thematic progression were used in delivering the message in different occurrences. Constant theme was used 11 times with the percentage 33,3%; linear theme was used 19 times with the percentage 57,6%; split rheme was used 2 times with the percentage 6,06% and derived pattern was used only once with the percentage 3%. From the analysis also found that the most thematic progression that used was linear theme pattern. The results of this study are to help the journalist in composing a coherent and cohesive business text and to make the reader easier to grasp the meaning of the business text.